(untitled) (Ustozlar uchun, 2025)
This article examines key methods of system analysis applied in the pedagogical process, highlighting their scientific basis, practical applicability, and effectiveness. System analysis enables educators to evaluate structural components and dynamics of the teaching–learning process, ensuring informed decision-making and improved pedagogical outcomes.